Correlation Between Energy Intake and Body Fat Percentage Aand The Cardiorespiratory Endurance of Wushu Athletes in "Klub Fighter" Banjarnegara - Dewani Saila Putri; Astrid Noviana (Sport and Nutrition Journal, 2025)
Cardiorespiratory endurance is one of the physical fitness components needed by an athlete. Several factors, including nutritional factors, can influence cardiorespiratory endurance. This study aimed to investigate the relationship between energy intake, body fat percentage, and cardiorespiratory endurance in “Klub Fighter” wushu athletes in Banjarnegara. This study used an observational analytical design with a cross-sectional approach. A total of 25 people were sampled to find the respondents. Energy intake data were obtained using the 3x24-hour food recall method, body fat percentage was measured through Bioelectrical Impedance Analysis (BIA), and cardiorespiratory endurance was assessed using the Bleep test. Data analysis employed the Spearman Rank correlation test, and multivariate testing utilized the multiple linear regression method. This study revealed that 60% of athletes had an energy intake deficiency, 48% had a body fat percentage in the deficiency category, and 60% had cardiorespiratory endurance (VO2Max) in the deficiency category. Energy intake was associated with cardiorespiratory endurance in "Klub Fighter" wushu athletes in Banjarnegara (p < 0.05). Body fat percentage is also related to the cardiorespiratory endurance of wushu athletes from "Klub Fighter" Banjarnegara (p < 0.05). A relationship was found between energy intake and body fat percentage, as well as cardiorespiratory endurance, in wushu athletes from "Klub Fighter" Banjarnegara.